The Effectiveness of Indonesia’s Feed-in-Tariff Implementation to Improve Business Interest in Renewable Energy Case: The Simulation for Solar Farm in Weh Island (Aceh-Indonesia) - Rahmawati, Sri; Salam, Rudi (IPTEK Journal of Proceedings Series, 2020)
The support of the Indonesian government in encouraging the achievement of renewable energy targets is to impose a Feed in Tariff (FiT) rule as a benchmark purchase price through the State Electricity Provider (PLN). The Ministry of Energy and Mineral Resources in 2013 determined that, the FiT for the Aceh region was $ 17 cents, where the highest FiT in Indonesia could reach $ 30 cents. In 2017 a new regulation was issued, in which FiT was set at 85% of regional production costs (BPP). In fact, currently BPP available on Weh Island reach more than Rp. 2,500 / kWh, with an average selling price to the community of Rp. 900, - / kWh. This BPP is more expensive than the price setting by the Government in 2017 of Rp 1,733 / kWh. In measuring the FiT's effectiveness, the evaluation solved based on economic valuation. Simulations were carried out for the capacity of 1 and 5 MW solar farms using 2 different panel components by comparing the prices of FiT BPP determined by the government and BPP in actual conditions. The results showed that, simulations with a capacity of 1 MW, using 85% of the government's BPP, were ineffective and not feasible based on economic calculations. whereas with FiT based on actual BPP, the profit to be achieved is about 42-45% / kwh with return-on-investment capital in the 10th year. The simulation with 5 MW capacity shows an effective and feasible profit if it use the actual BPP condition of the FiT with an effective profit value around 49-56% / kwh.